Pervious Geopolymer Concrete under Ambient Curing. (2021) - Chithambar Ganesh, A.; Vinod kumar, M.; Kanniga Devi, R.; Srikar, PavanVenkat; Prasad, SathyaVara; Manoj Kumar, M.; Sarath, R.P.
Abstract: The synthesis of cement concrete involves degradation to environment through land and air pollution through the liberation of harmful greenhouse gasses. This laid the evolution and development of geopolymer concrete. On the other hand there are problems caused due to the impervious concrete surfaces that restrict the passage of water to the ground. In this research, works have been focused to develop pervious geopolymer concrete using Ground Granulated Blast Furnace Slag (GGBFS) as the source material. Combination of NaOH and Na2 SiO3 solution was used as the alkaline solution. Usage of fine aggregate was eliminated and different proportions of GGBFS were tried to synthesis pervious geopolymer concrete of M 30 grade. Properties such as workability, compressive, permeability, tensile and flexural strength were determined. This research reveals the scope for the development of sustainable pervious concrete material.